2018
DOI: 10.1016/j.ajpath.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Argonaute 2 RNA Immunoprecipitation Reveals Distinct miRNA Targetomes of Primary Burkitt Lymphoma Tumors and Normal B Cells

Abstract: miRNAs are small noncoding RNAs involved in the posttranscriptional regulation of gene expression. Deregulated miRNA levels have been linked to Burkitt lymphoma (BL) pathogenesis. To date, the number of known pathogenesis-related miRNA-target gene interactions is limited. Here, we determined for the first time the miRNA targetomes of primary BL tumors and normal B cells. AGO2-RNA immunoprecipitation of two frozen diagnostic BL tissue samples and three CD19 B-cell samples isolated from routinely removed tonsils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…[50,94] For AGO2 RIP, TNFRSF12A mRNA was used as a positive control. [95] Ribosome Profiling and Ribo-seq Analysis: The ribosome profiling assay was conducted as previously described with minor modifications. [32] The curve was generated with optical scanning at 254 nm using a Gradient Profiler (BioComp).…”
Section: Methodsmentioning
confidence: 99%
“…[50,94] For AGO2 RIP, TNFRSF12A mRNA was used as a positive control. [95] Ribosome Profiling and Ribo-seq Analysis: The ribosome profiling assay was conducted as previously described with minor modifications. [32] The curve was generated with optical scanning at 254 nm using a Gradient Profiler (BioComp).…”
Section: Methodsmentioning
confidence: 99%
“…In humans, over 1000 miRNAs have been identified, and each miRNA potentially represses hundreds of target mRNAs [3]. Over the last several decades, there have been numerous studies that have found associations between miRNAs and various types of cancer, such as lymphocytic leukemia [4,5], lung cancer [6,7], colorectal neoplasia [8], Burkitt lymphoma [9], glioblastoma [10], tumor cell [11], B cell lymphomas of hepatocellular carcinoma (HCC) [12], oral squamous cell carcinoma [13], and breast cancer [14]. Relatedly, many biological techniques have been developed for miRNA detectors, including Northern blot [15], real-time PCR [16], oligonucleotide microarray [17,18], laser-induced fluorescence [19], microarray [20,21], and even various label-free techniques [22], as well as some strategy approaches for the detection of miRNAs, such as electrochemical, photoelectrochemical and optical fiber sensing methods.…”
Section: Introductionmentioning
confidence: 99%